2008
DOI: 10.1016/j.virol.2008.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of hepatitis B virus X gene phylogeny, genetic variability and its impact on pathogenesis: Implications in Eastern Indian HBV carriers

Abstract: HBx genetic variability was explored in the Eastern Indian population with low HCC incidence. DNase I sensitive HBV DNA was detected in 53% samples, which differed significantly between clinical groups (P<0.001). HBV genotypes A (Aa/A1), C (Cs/C1) and D (D1, D2, D3, D5) were detected in 37.5%, 18.7% and 43.7% samples respectively. Population specific signature HBx residues A(36), V(88), S(101) in Aa/A1 and residues P(41), Q(110) in D5 were detected. Mutations T(127), M(130) and I(131) were detected in 66.7%, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
27
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 48 publications
3
27
1
2
Order By: Relevance
“…Moreover, subgenotype Ae/A2 has not been detected in any of the group III serum HBV isolates in this study, despite the fact that they were extracted and amplified simultaneously with the PBL samples. In addition, a number of our other studies focused on serum HBV isolates, and in parallel or after this study, we have detected diverse HBV subgenotypes, namely, Aa/A1, Cs/C1, D1, D2, D3, and D5 (1,2,4,10,12,14), but subgenotype Ae/A2 with G145R was not detected, regardless of the fact that all of the studies were performed using the same experimental procedures, reagent sets, and laboratory facilities. These facts exclude the possibility that the detection of subgenotype Ae/A2, specifically in the PBL, across individuals in the present study was due to cross-contamination.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Moreover, subgenotype Ae/A2 has not been detected in any of the group III serum HBV isolates in this study, despite the fact that they were extracted and amplified simultaneously with the PBL samples. In addition, a number of our other studies focused on serum HBV isolates, and in parallel or after this study, we have detected diverse HBV subgenotypes, namely, Aa/A1, Cs/C1, D1, D2, D3, and D5 (1,2,4,10,12,14), but subgenotype Ae/A2 with G145R was not detected, regardless of the fact that all of the studies were performed using the same experimental procedures, reagent sets, and laboratory facilities. These facts exclude the possibility that the detection of subgenotype Ae/A2, specifically in the PBL, across individuals in the present study was due to cross-contamination.…”
Section: Discussionmentioning
confidence: 62%
“…lowed by genotypes C (subgenotype Cs/C1) and A (subgenotype Aa/A1) in our study population (1,2,3,4,12). Specifically, the incidence of HBV genotype Aa/A1 (the Afro-Asian subgenotype of genotype A) in the sera was found to be about 8 and 11% among the incidentally detected asymptomatic HBsAg-negative HBV carriers (occult HBV infection) and HBsAg-positive HBV carriers, respectively (2, 13).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…[11][12][13][14][15][16] In addition, HBV genotypes/subgenotypes and their related mutations in the HBx genome have been reported to be associated with HCC. Datta et al 17 collected the available literature focused on the functional significance of different HBx substitutions, and they found that the amino acid substitutions at position 5 (L/M), 31 (A), 38 (S) and 42 (P) have been reported to be significantly associated with HCC development in chronic hepatitis B patients in a particular genotype/subgenotype. However, whether these molecular virological factors in occult HBVinfected HCC patients resemble those in HBsAg-positive HCC patients have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several mutations in HBx gene region have been reported to be significantly associated with HCC development in a particular genotype/subgenotype. 17 However, it remained unclear whether these HBx substitutions were associated with occult HBV-infected HCC.…”
mentioning
confidence: 99%